2012
DOI: 10.2527/jas.2012-5184
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among performance, residual feed intake, and product quality of progeny from Red Angus sires divergent for maintenance energy EPD1

Abstract: Energy expenditure is a physiological process that may be closely associated with residual feed intake (RFI). The maintenance energy (ME(M)) EPD was developed by the Red Angus Association of America (RAAA) and is used as an indicator of energy expenditure. The objectives of this study were to evaluate and quantify the following relationships using progeny of Red Angus (RA) sires divergent for ME(M) EPD: 1) postweaning RFI and finishing phase feed efficiency (FE), 2) postweaning RFI and end-product quality, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(40 reference statements)
2
13
0
Order By: Relevance
“…Muscle pH and temperatures in this study were not measured during the early postmortem period, and no significant difference between RFI groups was observed for muscle temperature and pH at 72 h post mortem for all four muscles. In fact, selection for RFI did not affect the chemical composition of the four muscles from the different genetic groups, which is consistent with previous studies (Baker et al 2006;Ahola et al 2011;Welch et al 2012;Zorzi et al 2013;Nascimento et al 2016). Ahola et al (2011) found no significant difference in water and protein percentages, cooking loss, and juiciness across different RFI Angus steers, and Baker et al (2006) reported a tendency (not statistically significant) for protein and moisture of longissimus dorsi of Angus steers to be affected by RFI selection.…”
Section: Discussionsupporting
confidence: 89%
“…Muscle pH and temperatures in this study were not measured during the early postmortem period, and no significant difference between RFI groups was observed for muscle temperature and pH at 72 h post mortem for all four muscles. In fact, selection for RFI did not affect the chemical composition of the four muscles from the different genetic groups, which is consistent with previous studies (Baker et al 2006;Ahola et al 2011;Welch et al 2012;Zorzi et al 2013;Nascimento et al 2016). Ahola et al (2011) found no significant difference in water and protein percentages, cooking loss, and juiciness across different RFI Angus steers, and Baker et al (2006) reported a tendency (not statistically significant) for protein and moisture of longissimus dorsi of Angus steers to be affected by RFI selection.…”
Section: Discussionsupporting
confidence: 89%
“…Research efforts for years indicate that RFI is a powerful selection tool for improving feed efficiency and decreasing feed costs, especially in beef cattle (Herd et al, 2003;Arthur and Herd, 2008;Hoque and Suzuki, 2009). Because RFI is defined as the difference between actual feed intake and expected feed intake, most of these studies have been conducted on free-access feeding of cattle (Meyer et al, 2008;Welch et al, 2012) or sheep (Snowder and Van Vleck, 2003) using medium-to highenergy diets. However, it is important to know whether the animals that were efficient or inefficient on a feeding regime are also efficient or inefficient on other feeding conditions such as programmed or restricted feeding regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Energetic efficiency is an intricate process associated with and dependent on various factors, as noted above. Welch et al (2012) discussed sire ME M EPD in context of the relationship that may exist between maintenance energy and RFI, which also alluded to the importance of overall energetic efficiency. Based on this concept, measurements that could provide substantial input regarding variation in RFI were also analyzed in terms of sire ME M EPD.…”
Section: Discussionmentioning
confidence: 99%
“…For a more detailed description of sire selection, postweaning RFI evaluation, and finishing phase FE evaluation, refer to Welch et al (2012). In brief, a total of 12 Red Angus sires divergent for ME M EPD were chosen using the Red Angus Association of America-generated ME M EPD.…”
Section: Methodsmentioning
confidence: 99%